Understanding the adoption of modern cultivars in India: Adoption probability and use intensity - Varshney, Deepak; Joshi, Pramod Kumar; Roy, Devesh; Kumar, Anjani (Western Agricultural Economics Association, 2022)
Using a survey of 1,500 farmers, we identify farmer-level constraints to adoption of modern cultivars in Rajasthan, India, and decompose the overall elasticity into the elasticities of adoption probability and use intensity. We find that access to credit and intensity of extension services received drive adoption of modern cultivars, but both factors are more important for determining adoption probability than for determining use intensity. Moreover, the study assesses the roles that key traits of individual cultivars play in their adoption. Varietal traits significant for the adoption of modern cultivars vary by crop and geography. However, the main driver for continuing old cultivars across crops is taste attributes.